The Arctic zone of the Republic of Karelia: Search for ways of Development - Valery P. Zhuravel (Научно-аналитический вестник Института Европы РАН)
The Northern part of the territory of the Republic of Karelia belongs to the Arctic zone of the Russian Federation, which includes 6 municipalities. The article analysed the first stage of the implementation of the 8 tasks set out in paragraph 20 of the Strategy for Developing the Russian Arctic Zone and Ensuring National Security until 2035 («the 2035 Strategy») in relation to the Arctic zone of Karelia. Particular attention is paid to the analysis of the state and modernisation of the White Sea – Baltic Canal, the development of the building materials industry based on construction stone deposits, as well as the creation and development of mineral and raw materials centres of the East Karelian copper-gold-molybdenum ore zone. The activities on the formation of a cluster of deep wood processing enterprises, the development of the fisheries cluster, cultural, historical and ecological tourism and the development of international cooperation are analysed. The problem of creating cascades of small hydroelectric power plants in the region and a network of data processing and storage centres based on domestic high-speed ultra-dense solutions is considered. The article examines the dynamics of the population of Arctic municipalities, the experience of Arctic residents and their tax benefits.